EVALUASI KINERJA KEUANGAN PEMERINTAH KOTA YOGYAKARTA PERIODE ANGGARAN 2013 - 2017 - Beta Asteria (Jurnal Manajemen, 2019)
This research aims to evaluate financial performance of Yogyakarta City Government in fiscal period of 2013 to 2017 by using the specific Government Financial Ratios. Yogyakarta City Government’s liquidity performance, as seen in the results measured by using Current Ratio and Quick Ratio, has been in highest peak from its minimum-good-standard. The settlement for its current debts by using current assets is indicated risk-free though there found some non-optimum managements of current assets (assets components are too liquid). Government’s leverage performance, as seen in the results measured by using Debt to Regional Income Ratio and Debt to Regional Tax Ratio, has been in lowest peak from its maximum-good-standard. The settlement for its debts by using regional income and regional task is indicated risk-free. Government’s income management analysis, as seen in the results measured by Decentralization Degree is categorized in “acceptable” to be in “medium” stage. Meanwhile, the results measured by Regional Independence Ratio show us some moving-trends of local financial ability from “low” to be in “medium” level and relationship-pattern from “consultative” to be in “participatory” stage . Both ratios ensure that independence level of Yogyakarta City Government is still low though it keeps showing us increase as the years went by. The results measured by using Regional-Owned Enterprises Contribution Degree shows us that the contributions counted by Regional-Owned Enterprises are still very low. Government’s expenditure analysis, as seen in the results measured by using Capital Expenditure to Total Expenditure Ratio, shows us that Government’s capital expenditure through the fiscal years are still in the reasonable and fairness limit. The results measured by using Efficiency Ratio are both lower than the maximum standard of 100%. The governmental-budget-using is in “efficient” stage. There is no over-financing indicated.